Evaluation Antioxidant and Immunity Activities of Green Synthesized Selenium Nanoparticles by Extraction spirulina to reduces oxidative stress induced by phentermine in males rats - Hawraa Ali Sultan; Ali Noory Fajer (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Abstract. Background: Slimming drugs, such as phentermine, are widely used for weight reduction but are known to induce oxidative stress, particularly affecting hepatic and renal tissues. Selenium nanoparticles (SeNPs), especially those biosynthesized using natural sources like spirulina platensis, have demonstrated promising antioxidant and protective activities in biological systems. Objective: This study aimed to assess the protective effects of selenium nanoparticles synthesized from spirulina platensis extract on renal and hepatic functions in male rats exposed to phentermine induced oxidative stress. Methods: Twenty-six adult male wistar rats were divided into five experimental groups: control group (dosed with water n=5), SeNPs group (dosed with SeNPs n=5), phentermine group (dosed with phentermine n=5), SeNPs then phentermine group (dosed with SeNPs then phentermine n=5), phentermine then SeNPs group (dosed with phentermine then SeNPs n=5). The experiment lasted for 45 days, the measurement of cytokines IL-6, IL-12, TOS and TO-AC. Results: Phentermine administration significantly increased cytokines IL-6, IL-12 indicating marked oxidative stress and immune activation. Treatment with SeNPs alone or in combination with phentermine notably improved these parameters. The group dosed with SeNPs prior to phentermine (SeNPs then phentermine) showed the most prominent protective effects with values approaching those of the control. Conclusions: Selenium nanoparticles from spirulina platensis demonstrated significant protective, antioxidant, and immunomodulatory effects against phentermine induced immune disturbances. These findings support their potential